If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 7 = 1 + 5x Reorder the terms: 7 + 6x = 1 + 5x Solving 7 + 6x = 1 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 7 + 6x + -5x = 1 + 5x + -5x Combine like terms: 6x + -5x = 1x 7 + 1x = 1 + 5x + -5x Combine like terms: 5x + -5x = 0 7 + 1x = 1 + 0 7 + 1x = 1 Add '-7' to each side of the equation. 7 + -7 + 1x = 1 + -7 Combine like terms: 7 + -7 = 0 0 + 1x = 1 + -7 1x = 1 + -7 Combine like terms: 1 + -7 = -6 1x = -6 Divide each side by '1'. x = -6 Simplifying x = -6
| 4x-13=5(2x+1) | | 10x+12=76+x | | 2x^3+3x^2-12x-15=y | | Y=100+0.66(Y-200)+250+200+150 | | 3x+47=6x+15 | | Y=100+0.6(Y-200)+250+200+150 | | Y=400+0.5(Y-200)+250+200+150 | | Y=100+0.5(Y-200)+250+200+150 | | 7+ln(27x)=22-2ln(x) | | y(y-6)-6(y-6)= | | 5(x-2)-3(x-1)=0 | | a(a-4)-4(a-4)= | | c(c-5)-5(c-5)= | | m(m-2)-2(m-2)= | | p=(a+b)*2 | | t(t+4)+4(t+4)= | | y(y+2)+2(y+2)= | | Y=150+0.7(Y-200)+50+0.2+200 | | b(b+7)-7(b+7)= | | r(r+4)-4(r+4)= | | p(p-2)+4(p-2)= | | x-4540=40 | | Y=150+0.7(Y-200)+50+0.2Y+200 | | x(x+2)+3(x+2)= | | -7(x-3)=63 | | 342+x=442 | | 8(2+z)-5(3-2z)= | | 2-3x=5x-2(x+8) | | 3(4-5a)-2(5-4a)= | | x-240=10 | | 4(y-6)-5(3y-1)= | | 7-2(x-4.5)=6-4x |